2022
DOI: 10.1007/s13278-022-00998-2
|View full text |Cite
|
Sign up to set email alerts
|

A reliable sentiment analysis for classification of tweets in social networks

Abstract: In modern society, the use of social networks is more than ever and they have become the most popular medium for daily communications. Twitter is a social network where users are able to share their daily emotions and opinions with tweets. Sentiment analysis is a method to identify these emotions and determine whether a text is positive, negative, or neutral. In this article, we apply four widely used data mining classifiers, namely K-nearest neighbor, decision tree, support vector machine, and naive Bayes, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…For classification purposes, these rules separate data points into different classes. Predictions for class labels are made based on the majority of examples that reached each leaf node during the tree's construction [1].…”
Section: Decision Tree Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…For classification purposes, these rules separate data points into different classes. Predictions for class labels are made based on the majority of examples that reached each leaf node during the tree's construction [1].…”
Section: Decision Tree Classifiermentioning
confidence: 99%
“…Social networks like Twitter are rapidly growing, allowing people to share personal opinions and emotions. This rapid growth and data accessibility offer research potential for various applications, including customer, product, sector, and digital marketing [1]. The increasing prevalence of interactions with products, articles, and our friends' posts in the digital age underscores the growing importance of studying semantic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Masoud et al [1], data from two distinct datasets with different characteristics underwent analysis using four classification algorithms and ensemble techniques to enhance reliability. Surprisingly, the tests revealed that the use of a single algorithm slightly outperformed ensemble techniques.…”
Section: Literature Surveymentioning
confidence: 99%
“…It also reduces the error generated by a single classifier, namely overfitting. Recently, in the literature, classifier ensemble has been used in areas such as disease detection [6], social networks [7] and mood recognition [8]. In these articles, the authors adopted a classifier ensemble for the current context, which yielded good results.…”
Section: Classifier Ensembles and Choquet Integralsmentioning
confidence: 99%